CLIF-C AD score versus MELD score in predicting mortality in alcoholic liver cirrhosis patients - Goran Bokan; Zoran Mavija (Биомедицинска истраживања, 2021)
Introduction: Alcoholic liver cirrhosis is an advanced stage of progressive liver failure with an often adverse outcome. Numerous scoring systems are used to predict outcomes. The results of MELD Score (Model For End-Stage Liver Disease) and CLIF Consortium Acute Decompensation score (CLIF-C ADs) were used in this paper to determine which one is more reliable in predicting mortality. Methods: The value of CLIF-C AD and MELD scores using online calculator at the time of hospitalization was calculated. Follow-up has also started during hospitalization and control examinations in the next 3 months. Results: This study included 145 patients of both genders, diagnosed with alcoholic liver cirrhosis. During the first 3 months from the moment of the calculation of the score, 39 patients (32 male and 7 female patients) passed away, which represents 82.1% versus 17.9%. The mean age of patients was 59.18 ± 9.19 years. All CLIF-C AD scores of 99 and above had a 100% probability of death in the first 3 months. Conclusion: The CLIF-C AD score proved to be more reliable than the MELD score in predicting mortality in patients with alcoholic liver cirrhosis in the first 3 months.
Keywords: CLIF-C AD score; MELD score; alcoholic liver cirrhosis